Sedimentary Geology - Sedimentary Geology (Elsevier, 2026)
Sedimentary Geology is a journal that rapidly publishes high quality, original research and review papers that cover all aspects of sediments and sedimentary rocks at all spatial and temporal scales. Submitted papers must make a significant contribution to the field of study and must place the research in a broad context , so that it is of interest to the diverse, international readership of the journal. papers that are largely descriptive in nature, of limited scope or local geographical significance, or based on limited data will not be considered for publication.
FI 1.32
Q1
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Geología; Geofísica; Acuerdos transformativos; Transformative agreements; Sedimentos; Rocas sedimentarias